Umberto Eco's The Name of the Rose and Intertextuality: Eastern Themes. - ABDOLLAHI, MANIZEH (Scripta, 2020)
The Name of the Rose, first novel by Umberto Eco, the Italian novelist and semiotician was published in 1980. The story happens in the Middle Ages (14th century) in an abbey, having a large and wonderful library. This historical detective story is a complicated novel full of intricate signs and symbols. In this paper, some of the themes of The Name of the Rose found in Eastern texts are discussed that indicate intertextuality and the immense amount of knowledge that Eco had of literature. It is stated that the frame tale is very much similar to Kalila va Demna and some of the subplots of the novel have similarities with stories from ancient Iran and the Middle East.